EPISIOTOMY IN BRAZIL: A NARRATIVE REVIEW IN AN EVIDENCE BASED PERSPECTIVE - Aragão, Júlio César Soares; Ferreira, Maria Cecília Siqueira; Padilha, Marília Barros; Freitas, Maria Martha Rennó Ribeiro Chaves (Revista Feminismos, 2020)
Episiotomy, an incision used in obstetrical practice, has been shrouded by much controversy in recent decades. In order to discuss the practice of episiotomy and its complications, a narrative review was carried out on publications on this topic between 2007 and 2017. Currently classified as category D by the World Health Organization, episiotomy adoption as a routine practice is unjustified and harmful, and selective use is still debatable. It is a obstetric violence category and increases short and long term complications. Brazilian obstetricians ignore scientific evidence and it is imperative to reformulate practices and update professionals regarding outdated practices.